TWEEC: Computer‐aided glaucoma diagnosis from retinal images using deep learning techniques. Issue 1 (4th July 2021) - Abdel‐Hamid, Lamiaa
Abstract: A novel two‐branched deep convolutional (TWEEC) network is developed for computer‐aided glaucoma diagnosis. The TWEEC network is designed to simultaneously extract anatomical information related to the optic disc and surrounding blood vessels which are the retinal structures most affected by glaucoma progression. The spatial retinal images and wavelet approximation subbands are compared as inputs to the proposed network. TWEEC's performance is compared to three implemented convolutional networks, one of which employs transfer learning. Experiments showed that the introduced TWEEC network achieved accuracies of 98.78% and 96.34% for the spatial and wavelet inputs, respectively, by that outperforming the other three deep networks by 8‐15%. This work paves the way for the development of efficient deep learning based computer‐aided glaucoma diagnosis tools. Moreover, the present study illustrates that considering specific wavelet subbands for the training of convolutional networks can result in reliable performance with the advantage of reduced overall network training time.